Nonmetal-Mediated Atomic Spalling of Large-Area Monolayer Transition Metal Dichalcogenide - Kim, Sein; Kim, Seung Il; Ghods, Soheil; Kim, Jin Su; Lee, Young Cheol; Kwun, Hyung Jun; Moon, Ji Yun; Lee, Jae Hyun (Small Science, 2023)
Transition metal dichalcogenides (TMDCs) have attracted intense interest; however, despite the considerable effort of researchers, a universal manufacturing method that can guarantee both high material quality and throughput has not been realized to date. Herein, a universal approach to producing high-quality monolayer TMDCs on a large scale via germanium (Ge)-mediated atomic spalling is presented. Through the modified analytic model, the study verifies that the thin Ge film could be a suitable stressor that effectively reduces the crack propagation depth at the sub-nanometer range. In particular, an acid-etching process is not required in the overall atomic spalling process due to the water-soluble nature of the Ge, enabling it widely applicable to various TMDCs. Under the optimized spalling conditions, a millimeter-sized monolayer of stable MoS2, as well as unstable MoTe2, is successfully achieved. Through detailed spectroscopic and electrical characterizations, it is confirmed that the proposed methodology for obtaining large-area atomic layers does not introduce any significant structural defects or chemical contaminations.
Keywords: atomic spalling; germanium; monolayers; transition metal dichalcogenides; wet etching